(untitled) (Global Journals of Research in Engineering, 2020)
Given the description of construction are given the fundamental characteristics of the small storage batteries Li of group. The fundamental characteristics of the nickel metal hydride storage batteries are given Ni-MH. Development and application of such storage batteries significantly increased the reliability of small mobile radio sets, in particular, cell phones.